Pengaruh Tiktok Terhadap Perkembangan Bahasa di Kalangan Generasi Alpha - Anhar, Anhar; Khoirunnisaa, Khoirunnisaa; Septianti, Lisa; Asmawati, Mala (Indo-MathEdu Intellectuals Journal, 2024)
This study explores the influence of TikTok on the language development of Generation Alpha in Indonesia, a generation born after 2010 and raised in a digital environment. Using a qualitative descriptive approach, this research employs in-depth interviews, observation, and content analysis to examine how TikTok affects vocabulary, the emergence of new terms, and communication patterns. The findings reveal that TikTok contributes to the rise of neologisms and slang terms such as "rizz," "brainrot," and "sigma," which have quickly spread among Generation Alpha. This trend enriches vocabulary while also driving changes in formal language norms, although concerns remain regarding a decline in formal language proficiency. This study provides insights into the dynamics of language in the digital age and its implications for language education policy